Characteristics and Treatment Strategy of Isolated Calf Deep Venous Thrombosis after Fractures: A Review of Recent Literature - Wei‐Guang Zhao; Ji‐Ying Yan; Xiao‐Lei Li; Cai‐Ying Shi; Zhi‐Yun Wang; Wei Guo; Kai Zhang; Wei‐Li Zhang; Xiao‐Chuan Jia; Shu‐Bei Cui; Li‐Qiang Jiang; Jian‐Long Zhao; et al. (Orthopaedic Surgery, 2022)
Isolated calf deep venous thrombosis (ICDVT) includes thrombosis located at the far end of the popliteal vein, such as the anterior tibial vein, posterior tibial vein, fibular vein, and intramuscular vein of the soleus and gastrocnemius. This type of thrombosis has the highest incidence, accounting for approximately half of all deep vein thrombosis (DVT) cases; however, there is no consistent recommendation for ICDVT treatment across countries, and there is also no optimal management strategy. In recent years, increasing evidence has shown that ICDVT can develop into proximal DVT, even causing pulmonary embolism (PE). Therefore, some experts suggest anticoagulant therapy for this type of DVT, while others hold an opposing attitude. Therefore, the treatment strategy for this type of DVT has become a hot and difficult research topic. The purpose of this review is to summarize the characteristics of ICDVT and the effects of different treatment strategies by analyzing recent and important classical works in the literature in an attempt to provide recommendations for the treatment of this most common type of DVT in orthopaedic clinics.